2011
DOI: 10.1111/j.1751-1097.2011.00996.x
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Proton‐Coupled Electron Transfers in Biorelevant Phenolic Systems

Abstract: Proton-coupled electron transfer (PCET) reactions have received much attention over the past 10 years, from an experimental as well as from a theoretical point of view. At the heart of many chemical and biological processes, such reactions are of particular interest in energy conversion and enzymatic processes. Among the numerous examples of PCET reactions, photosynthesis and particularly reactions inside the Photosystem II (PSII) subunit, involving a global four electrons and four protons process to perform w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 222 publications
(254 reference statements)
1
30
0
2
Order By: Relevance
“…The RPD values (> 2.5) indicated that the calibration models were adequate to measure phenolic compounds as low, medium, and high, qualitatively. Results from this study agree with those reported in Cabernet Sauvignon by other authors using Raman spectroscopy [23,24]. SECV: standard error of cross-validation, SD: standard deviation, RPD: residual predictive deviation (SD/SECV) value, R 2 : coefficient of determination in cross-validation.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The RPD values (> 2.5) indicated that the calibration models were adequate to measure phenolic compounds as low, medium, and high, qualitatively. Results from this study agree with those reported in Cabernet Sauvignon by other authors using Raman spectroscopy [23,24]. SECV: standard error of cross-validation, SD: standard deviation, RPD: residual predictive deviation (SD/SECV) value, R 2 : coefficient of determination in cross-validation.…”
Section: Resultssupporting
confidence: 91%
“…It has been reported that the strong fluorescence background associated with the absorption of hydroxycinnamic acids (phenolics) and related phenolic compounds determine a Raman shift depending on the excitation [18][19][20][21][22], where, the observed emission in the wines is attributed to the excited state proton transfer [23,24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…54,55 However, such hydrogen bonds rather increase the electron donating capacity of the amino group, thus favoring the formation of the ICT state. Datta et al showed that the ICT emission of 3-aminoquinoline (20) was favored in aprotic solvents such as dimethyl sulfoxide by a similar type of hydrogen bonding (21). 56 On the other hand hydrogen bonding inhibits the ICT emission of 20 in protic solvents, where the charge donor acts as a hydrogen bond acceptor 22, but the protonation of the acceptor enhances the ICT process (23).…”
Section: Role Of Hydrogen Bonding With An Electron Donormentioning
confidence: 99%
“…We employ the new approach to investigate the reaction dynamics of condensed-phase protoncoupled electron transfer (PCET), an important prototype for quantum systems that exhibit multiple reaction pathways [12][13][14][15][16][17][18] . Numerical results demonstrate the practicality and utility of the new method for the mechanistic analysis of coupled quantum dynamical processes.…”
Section: Introductionmentioning
confidence: 99%